THE EFFECTIVITY OF THE GATE FOR PERSONS WITH DISABILITIES SUCCESS (GENDIS) PROGRAM ON THE INDEPENDENCE OF PERSONS WITH DISABILITIES IN BANYUMAS REGENCY - Suryoto, Suryoto; Saputra, Anggara Setya; Agustina, Alfriansa (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2023)
The increase in the growth of the number of employees with disabilities in Central Java Province was 4.9% while other provinces experienced a decrease in the number of employees with disabilities. The increase in the number of employees shows that the Provincial Government of Central Java is paying more attention to the government's responsibility to persons with disabilities through providing jobs and guarantees of a decent life for persons with disabilities in Central Java Province. The Government of Banyumas Regency held an innovative Gendis Program to improve the quality of life for persons with disabilities to make them more prosperous. This program became the Top 99 National Level Public Service Innovations. This study aims to determine the effect of the effectiveness of the Gendis program on the independence of persons with disabilities in Banyumas Regency. The study used quantitative research methods with data analysis techniques, Product Moment correlation test and Kendall Tau Correlation Test. Based on the results carried out, there is a positive and significant relationship between program effectiveness and disability independence where the better the program effectiveness, the better the independence of the disabled, and the results of the Kendall Tau Correlation there is a significant relationship between program effectiveness and independence variables. The program effectiveness variable has a Correlation Coefficient score of 0.713 with independence, which means that the closeness of the relationship between the two variables is strong and the direction of the relationship is positive.